2015
DOI: 10.5507/ag.2015.010
|View full text |Cite
|
Sign up to set email alerts
|

The impact of obesity on foot morphology in women aged 48 years or older

Abstract: As a result of postmenopausal changes; body fat mass (kg) rises in women by 0.4 kg/year to the age of 50, then to 75 years it rises more rapidly and then slightly decreases thereafter (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…We have indicated that there are no statistically significant association between BFP and muscle mass percentage with digit deformities (ALFA, BETA). However, there are reports claiming that, in adulthood, excessive weight contributes to the development of hallux varus, hallux valgus, digitus quintus varus, widening of the heel area, and heel misalignment [3,6,27,32]. Considering the fact that adolescents with excessive adipose tissue often remain obese in adulthood, musculoskeletal complications of childhood obesity may aggravate at a later age.…”
Section: Discussionmentioning
confidence: 99%
“…We have indicated that there are no statistically significant association between BFP and muscle mass percentage with digit deformities (ALFA, BETA). However, there are reports claiming that, in adulthood, excessive weight contributes to the development of hallux varus, hallux valgus, digitus quintus varus, widening of the heel area, and heel misalignment [3,6,27,32]. Considering the fact that adolescents with excessive adipose tissue often remain obese in adulthood, musculoskeletal complications of childhood obesity may aggravate at a later age.…”
Section: Discussionmentioning
confidence: 99%
“…18 The previous study by Tomankova (2015) revealed that subjects with a lower arch appeared to have a greater BMI. 5 Accordingly, other study showed that low arch of midfoot cause malalignment of the proximal lower extremity, frequently leading to structural and functional deficits. 1 The presence of excessive low arch leading to calcaneal eversion generates valgus of the knee joint, internal rotation of the tibia and femur.…”
Section: Discussionmentioning
confidence: 99%
“…Also, weight gain is associated with increased plantar midfoot pressure and functional limitations related with the foot. 2,4 The significant results of a study performed by Tomankova (2015), showed that excess body weight is a potential predictor of greater plantar pressure peak under the midfoot. 5 Increasing midfoot plantar pressure commonly followed by the loss of the longitudinal midfoot arch, resulting in pronation of the foot.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a higher BMI has profound effects on softtissue structures, such as tendons fascia and cartilage Obesity is considered a predictor of postural stability and a high BMI is an important risk factor for falling 4 . Obesity and being overweight are major risk factors for many chronic diseases 5 . Being overweight and obese are associated with a musculoskeletal state and are responsible for significant disabilities and impaired quality of life 6 .…”
Section: Introductionmentioning
confidence: 99%